Hyoscyamine 6β-Hydroxylase, a 2-Oxoglutarate-Dependent Dioxygenase, in Alkaloid-Producing Root Cultures - Hashimoto, Takashi (1986)
Root cultures of various solanaceous plants grow well in vitro and produce large amounts of tropane alkaloids. Enzyme activity that converts hyoscyamine to 6β-hydroxyhyoscyamine is present in cell-free extracts from cultured roots of Hyoscyamus niger L. The enzyme hyoscyamine 6β-hydroxylase was purified 3.3-fold and characterized. The hydroxylation reaction has absolute requirements for hyoscyamine, 2-oxoglutarate, Fe(2+) ions and molecular oxygen, and ascorbate stimulates this reaction. Only the l-isomer of hyoscyamine serves as a substrate; d-hyoscyamine is nearly inactive. Comparisons were made with a number of root, shoot, and callus cultures of the Atropa, Datura, Duboisia, Hyoscyamus, and Nicotiana species for the presence of the hydroxylase activity. Decarboxylation of 2-oxoglutarate during the conversion reaction was studied using [1-(14)C]-2-oxoglutarate. A 1:1 stoichiometry was shown between the hyoscyamine-dependent formation of CO(2) from 2-oxoglutarate and the hydroxylation of hyoscyamine. Therefore, the enzyme can be classified as a 2-oxoglutarate-dependent dioxygenase (EC 1.14.11.-). Both the supply of hyoscyamine and the hydroxylase activity determine the amounts of 6β-hydroxyhyoscyamine and scopolamine produced in alkaloid-producing cultures.